Effect of psychosocial work factors on the risk of depression: a protocol of a systematic review and meta-analysis of prospective studies - Mahée Gilbert-Ouimet; Chantal Brisson; Xavier Trudel; Michel Vézina; Lynne Moore; Caroline S Duchaine; Karine Aubé; Ana Paula Bruno Pena Gralle; Ruth Ndjaboue; Victoria K Massamba; Alain Lesage; Danielle Laurin (BMJ Open)
Introduction Depression is a common and disabling health problem that contributes to an important social and economic burden, particularly among the working age population. The deleterious effect of psychosocial work factors on depression has been documented. However, the most recent systematic reviews had restrictive eligibility criteria and, since their publications, several original studies have been published. The proposed systematic review aims to update, evaluate and synthesise the effect of psychosocial work factors from three recognised theoretical models, the demand-control-support, effort-reward imbalance and organisational justice models, on the risk of depression among workers.Method and analysis A systematic literature search will be conducted in seven academic databases (Medline, Embase, CINAHL, Web of Science, PsycInfo, Sociological abstracts and IBSS) as well as three grey literature databases. The search strategy was first run on January 2017, updated in October 2017 and will be updated 6 months prior to submission for publication. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations, study selection will be carried out using a rigorous multistep screening process in duplicate by independent reviewers. Prospective studies evaluating the effect of at least one psychosocial work factor from the three theoretical models on depression or antidepressant medication use among working adults will be included. Extracted data will be used for evidence synthesis as well as to assess risk of bias and methodological quality. Meta-estimates will be provided after considering homogeneity and number of studies.Ethics and dissemination This study will only draw from published studies and grey literature available in electronic databases; ethics approval is not required. The results of this review will be published in a peer review journal and presented at relevant conferences. Given that psychosocial work factors are frequent and modifiable, the results can help reduce the social and economic burden of depression and support public policy-makers to improve occupational health standards.PROSPERO registration number CRD42018107666